From concepts to practical tools of support: Development of the creative sector in Warsaw - Dudek-Mańkowska, Sylwia; Fuhrmann, Magdalena (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2012)
Warsaw is a metropolitan city with great creative potential. All the national media as well as editorial offices of most newspapers and periodicals of national circulation are located here. Mass media, educational institutions, and cultural institutions along with a community of educated and affluent people make Warsaw a leading cultural centre both in terms of potential in creative activities and as a market for products coming from the creative sector. Although the creative sector seems to be treated as an important part of the economic base of Warsaw’s development, creative potential located in the city seems to be underused. The goal of this paper is to present the support of city authorities for the development of the creative sector in Warsaw. The evaluation of problems and bottlenecks articulated by representatives of the creative sector will be confronted with the opinions of representatives of the City Hall.
Keywords: creative sector; creativity; Warsaw